Optimal Phase Balancing Planning for Loss Reduction in Distribution Systems using a Specialized Genetic Algorithm (2012)
The unbalanced operation of distribution systems impairs the quality of power and increases investment and operation costs. Feeder reconfiguration and phase exchange are the two main approaches to phase balancing, the first being the most difficult to carry out due to the small number of sectionalizers available in most distribution systems. On the other hand, the exchange of phases constitutes a direct, effective and low-cost alternative for the phase balance. The main contribution of this article is the proposal of an optimization model and a solution technique for phase balance planning in distribution systems. As for the optimization model, a mixed integer nonlinear formulation is proposed. On the other hand, the proposed solution technique consists of a specialized genetic algorithm. To show the effectiveness of the proposed methodology, several tests are carried out with two distribution systems of 37 and 19 bars, the latter with different load models. The results show that in addition to achieving the main objective of reducing losses, the phase balance allows obtaining other technical benefits such as the improvement of the stress profile and reduction of congestion in the system lines.